Transforming traditional Tai Ji Quan techniques into integrative movement therapy-Tai Ji Quan: Moving for Better Balance - Fuzhong Li (Elsevier, 2014)
Tai Ji Quan, developed as a martial art, has traditionally served multiple purposes, including self-defense, competition/performance, and health promotion. With respect to health, the benefits historically and anecdotally associated with Tai Ji Quan are now being supported by scientific and clinical research, with mounting evidence indicating its potential value in preventing and managing various diseases and improving well-being and quality of life in middle-aged and older adults. The research findings produced to date have both public health significance and clinical relevance. However, because of its roots in the martial arts, transforming traditional Tai Ji Quan movements and training approaches into contemporary therapeutic programs and functional applications is needed to maximize its ultimate utility. This paper addresses this issue by introducing Tai Ji Quan: Moving for Better Balance, a functional therapy that involves the use of Tai Ji Quan principles and Yang-style-based movements to form an innovative, contemporary therapeutic approach that integrates motor, sensory, and cognitive components to improve postural control, gait, and mobility for older adults and those who have neurodegenerative movement impairments. It provides a synergy of traditional and contemporary Tai Ji Quan practice with the ultimate goal of improving balance and gait, enhancing performance of daily functional tasks, and reducing incidence of falls among older adults.